BENANG MERAH PEREDARAN NARKOBA DI KOTA BATAM DAN STRATEGI PENANGGULANGANNYA - Bobby Mandala Putra; Harmiati Harmiati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Prof Dr Hazairin, SH, 2021)
MCases of abuse of Narcotics and illegal drugs (Drugs) in Indonesia are currently increasing. Batam City is one of the cities that has a significant influence on the increase in cases of drug abuse and trafficking in Indonesia. This is what makes Batam City the main destination for drug trafficking. This paper will unravel the common thread of drug trafficking in Batam City and the strategies for dealing with it. This type of research is descriptive qualitative research. The results of the study show that there are 5 factors causing Batam to become the main destination for drug trafficking, namely: (1) the high number of drug users in Indonesia, Riau Islands and Batam; (2) the lifestyle of the Indonesian people who are easily influenced into users, dealers and drug dealers; (3) Geographical location of Batam city; (4) The legal sanctions received by convicts in drug cases have not yet produced a deterrent effect; (5) The ratio of security forces and objects being monitored is not ideal; There are 4 strategies that can be applied to minimize the entry of drugs from within and outside the country into Batam: (1) reducing the number of drug users in Indonesia, Riau Islands and Batam; (2) improving the lifestyle of the Indonesian people so that they are not influenced by being a drug user, dealer or dealer; (3) increase the number of security and law enforcement officers tasked with supervising vital objects that have the potential to become entry points for drug trafficking in Batam and increase the budget; (4) imposing the most severe criminal penalties on convicts in drug cases so that those who have not been caught are deterrents or potential perpetrators of drug crimes. The results of this study are expected to be material for consideration of relevant stakeholders in overcoming drug trafficking and overcoming it.